Os periódicos "ciência hoje" e "ciência e cultura" e a divulgação da ciência no Brasil - Hernández-Canãdas, Patricia Liset (1987)
Bibliometric analysis fo the two journals published by the "Brasilian Society for the Advancement of Science" (SBPC) - "Ciência Hoje" and "Ciência e Cultura" - in order to verify: a) in which communication model both are inserted; b) the patterns of integration of the information they convey; c) to which degree they are answering to their objectives, and d) the degree of .similarity of their structural aspects. Regarding the information they convey and the public they aim at, "Ciência Hoje" can be considered as a journal for the "popularisation of science", while "Ciência e Cultura" is a journal which "disseminates" science. The former presents some aspects typically found in scientific communication, and the latter all of them, except for the half-life of the cited literature. It was also verified the enormous dependence on foreing literature, and a low level of integration among Latin American countries. Recommendations are made regarding the need for further studies on popularization and dissemination of science vehicles, as well as, their social, political and economical implications, all fundamental for the formulation of both· information and scientific and technological national policies.